USE OF LIMBERG FLAP FOR PILONIDAL SINUS-A VIABLE OPTION - Aslam, Muhammad Nadeem; Shoaib, Sidra; Choudhry, Abdul Majeed (Journal of Ayub Medical College Abbottabad, 2009)
Background: Pilonidal sinus disease has been treated for a long time with conventional open excision technique. The rhomboid flap of Limberg is a transposition flap that has been pleaded for treatment of this condition. Methods: We present our experience with the Limberg technique for both primary and recurrent pilonidal sinuses. One hundred and ten patients, with pilonidal sinus disease were treated with rhombic excision and Limberg transposition flaps. All sinus tracts were resected en bloc, and the fasciocutaneous Limberg flap was prepared from the gluteal region and closed it with a suction drain. Results: Full primary healing was obtained in 110 patients, 1 patient had minimal necrosis of flap and 2 had gaping of flap. Minor infection occurred in 3 patients. But all these complications healed uneventfully. The average hospital stay was 3 days. Follow up period was 1 year and 1 recurrence occurred. Conclusions: Limberg transposition flap is a promising surgical technique to treat pilonidal sinus. Keywords: Pilonidal sinus, Limberg flap, rhomboid transposition flap, fasciocutaneous flap, primary